2011
DOI: 10.1111/j.1524-475x.2011.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

High cell density attenuates reactive oxygen species: Implications for in vitro assays

Abstract: In vitro cell-based assays are an essential and universally used step in elucidation of biological processes as well as in drug development. However, results obtained depend on the validity of protocols used. This statement certainly pertains to in vitro assays of oxidative stress. The holy grail of in vitro models is reliability and predictability of outcomes that relate to a single variable like addition of hydrogen peroxide or xanthine oxidase. Without such validated outcomes, comparison of results among di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…quiescence) in confluent cultures and also of quiescent cells being less sensitive to DNA damage-induced cell death are both well-established concepts in cell biology. An additional mechanism has also been proposed for the reduced sensitivity of high-density cultures to oxidative stress based on their having a greater antioxidant capacity per well, which results in greater quenching of extracellular reactive oxygen species [15]. Consistent with these phenomena and our observations, it has been previously reported that confluent HaCaT cells are more resistant to oxidative stress than their subconfluent counterparts [16].…”
Section: Resultssupporting
confidence: 90%
“…quiescence) in confluent cultures and also of quiescent cells being less sensitive to DNA damage-induced cell death are both well-established concepts in cell biology. An additional mechanism has also been proposed for the reduced sensitivity of high-density cultures to oxidative stress based on their having a greater antioxidant capacity per well, which results in greater quenching of extracellular reactive oxygen species [15]. Consistent with these phenomena and our observations, it has been previously reported that confluent HaCaT cells are more resistant to oxidative stress than their subconfluent counterparts [16].…”
Section: Resultssupporting
confidence: 90%
“…Previous research suggests that cell density is pivotal in regulating neural precursor cell function, influencing the expression levels of various proteins and reactive oxygen species (ROS) [56]. Additionally, cell density is directly associated with resistance to oxidative stress [57], as well as cell differentiation, survival, migration, and proliferation [58, 59].…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study using dermal fibroblasts, Kim et al demonstrated that high cell densities led to improved ROS resistance by increasing the total antioxidant capacity of the cell culture [157]. The authors suggested that cell density should be considered as a critical point when studying oxidative stress.…”
Section: Measurement Of Reduced Glutathione Contentmentioning
confidence: 99%